THE CORRELATION OF ADOLESCENT KNOWLEDGE ABOUT FREE SEX PRACTICES WITH THE RISK OF CERVICAL CANCER ON THE MOTIVATION OF HPV VACCINATION AT JUNIOR HIGH SCHOOL 6 SURABAYA - Arlean, Maria Agatha; Dewanti, Linda; Setyowati, Dewi (Indonesian Midwifery and Health Sciences Journal, 2024)
Background: Cervical cancer had the second position as the leading cause of cancer towards woman in worldwide. The prevalence of cervical cancer in Indonesia reaches 23,4 cases from 100.000 population (Kemenkes RI, 2019). To enhance awareness and knowledge about HPV vaccination and cervical cancer, it is imperative to disseminate information through early health promotion regarding cervical cancer prevention, including HPV vaccination, and avoiding behaviors that may elevate the risk of cervical cancer, such as engaging in unprotected sexual activities. The aim of this study is to determine the correlation between adolescents' knowledge of "Free Sexual Practices with Cervical Cancer Incidence Risk" towards motivation for HPV vaccination at 6 Junior High School Surabaya. Method: The quantitative cross-sectional approach involved 304 students from grades 7, 8, and 9, selected through stratified sampling and was analyzed using the Spearman analysis test. Results: The majority (83.1%) of adolescents in grades 7, 8, and 9 demonstrated good knowledge (83.1%) regarding free sexual practices with the risk of cervical cancer incidence. A considerable number of adolescents (29.9%) in grades 7, 8, and 9 showed a moderate level of motivation. There is a significant correlation between the knowledge level regarding cervical cancer and the risk of cervical cancer incidence concerning motivation for HPV vaccination, with a p-value of 0.000 (p < 0.05). Conclusion: There is a correlation between the knowledge level regarding cervical cancer and the risk of cervical cancer incidence concerning motivation for HPV vaccination at 6 Junior High School Surabaya.